Quasi one-dimensional approach to evaluate temperature dependent anisotropic thermal conductivity of a flat laminate vapor chamber. (5th January 2019) - Mizuta, K.; Fukunaga, R.; Fukuda, K.; Nishino, T.; Goshima, T.; Nii, S.; Asano, T.
Highlights: Quasi 1D approach was employed to evaluate anisotropic thermal conductivity. The present method has sufficient accuracy for practical use. The value of kr of FGHP increased with increasing bottom temperature ( T btm ) The value of kr of FGHP exceeded 10, 000 W m −1  K −1 when T btm reached 360 K. The value of kz of FGHP was nearly constant when T btm was higher than 350 K. Abstract: A quasi one-dimensional approach was adopted to evaluate temperature dependent anisotropic thermal conductivity of a flat laminate vapor chamber called FGHP (Fine Grid Heat Pipe). Analytical models were derived for radial and axial thermal conductivity, respectively, and validated by comparing with the numerically obtained results. The shape of the heat spreader was 50 mm square, and 2 mm thick. Various conditions in the values of radial and axial thermal conductivities of heat spreader were tested for validation. Thermal conductivities evaluated with the present scheme were in good agreement with the true values both in isotropic and anisotropic cases. The average errors in evaluating radial and axial thermal conductivities utilizing the present scheme were 0.88% and 4.1%, respectively, which implies that the accuracy of the present scheme is acceptable for the practical cases. Application of the present scheme to the experimental results suggested that evaluated thermal conductivities both in radial and axial directions are in good agreement with its physical properties and that heat transfer characteristics of FGHP was anisotropic and varied with temperature. Moreover, the radial thermal conductivity of FGHP exceeded 10, 000 W m −1  K −1 when the bottom temperature reached 360 K, which is about twenty five times larger than that of copper heat spreader.